IMPLIKASI PENGGUNAAN METODE QIRAATI UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QURAN ANAK USIA DINI PADA PENDIDIKAN INKLUSI - Riris Wahyuningsih (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This study aims to find out the effectiveness of the use of Qiro'ati method to improve the ability to read the Qur'an in early childhood in PAUD AN-NUR Bulurejo Banyuwangi. This research method uses qualitative approach with case study design, revealing descriptively a phenomenon or event in a location that prioritizes natural or natural. The results showed an improvement in the ability to read the Qur'an in early childhood because of the use of the Qiraati method, evidenced by the output obtained by graduate students of the institution has better abilities than schools that do not use the Qiraati method, even graduates of PAUD AN-NUR Bulurejo Banyuwangi have been very fluent in reading the Qur'an even khotam, the most important is that graduate students have humanist traits and high discipline because it is as Important pek in the use of Qiraati method is discipline and istiqomah. Qiraati method has an important aspect that must exist, namely the preparation and learning that must be different from other methods, targets and clear rules that should not be broken at all, thus making this school different from other schools.